2001
DOI: 10.1002/mus.1103
|View full text |Cite
|
Sign up to set email alerts
|

Muscle glycogenoses

Abstract: There are 11 hereditary disorders of glycogen metabolism affecting muscle alone or together with other tissues, and they cause two main clinical syndromes: episodic, recurrent exercise intolerance with cramps, myalgia, and myoglobinuria; or fixed, often progressive weakness. Great strides have been made in our understanding of the molecular bases of these disorders, all of which show remarkable genetic heterogeneity. In contrast, the pathophysiological mechanisms underlying acute muscle breakdown and chronic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 147 publications
(152 reference statements)
4
74
0
2
Order By: Relevance
“…With regard to the latter proposition, it is interesting that Stbd1 binds better to plant amylopectin or glycogen from Epm2a Ϫ/Ϫ mice. Both amylopectin and Epm2a Ϫ/Ϫ glycogen are less branched than normal glycogen, similar to the polyglucosans associated with other glycogen storage diseases, including Andersen disease, Adult polyglucosan disease, and Tarui disease (51). Evidently, aberrantly branched glycogen in cells is to be avoided, and Stbd1 could selectively target such abnormal glycogen for transport to lysosomes and for subsequent disposal.…”
Section: Discussionmentioning
confidence: 92%
“…With regard to the latter proposition, it is interesting that Stbd1 binds better to plant amylopectin or glycogen from Epm2a Ϫ/Ϫ mice. Both amylopectin and Epm2a Ϫ/Ϫ glycogen are less branched than normal glycogen, similar to the polyglucosans associated with other glycogen storage diseases, including Andersen disease, Adult polyglucosan disease, and Tarui disease (51). Evidently, aberrantly branched glycogen in cells is to be avoided, and Stbd1 could selectively target such abnormal glycogen for transport to lysosomes and for subsequent disposal.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly a general impairment of energy metabolism have been observed in conditions of muscle atrophy [29], which may develop also during statin myopathy [50]. Moreover, it has been shown that hereditary muscle glycogenoses in humans are characterized by defective glycolytic enzymes, including beta enolase, and leads to different degree of myopathy, ranging from cramps to myoglobinuria [51][52]. The PK is a key enzyme in the glycolytic pathway, being responsible for the synthesis of pyruvate and ATP formation; it is allosterically inhibited by the increase in acetyl CoA, which in this condition may be induced by the block of cholesterol pathway in the cytosol.…”
Section: Glycolytic Metabolismmentioning
confidence: 99%
“…The primary polymerization in glycogen is via ␣-1,4-glycosidic linkages, formed by the action of glycogen synthase, with branchpoints created by ␣-1,6-glycosidic linkages introduced by the branching enzyme (1). Mutations in these and other glycogen metabolizing enzymes result in a series of glycogen storage diseases characterized by aberrant glycogen deposits (2)(3)(4). Lafora disease (OMIM254780) is an autosomal recessive juvenile-onset myoclonus epilepsy that, although not normally viewed as a classic example of a glycogenosis, nonetheless is characterized by abnormal glycogen accumulation.…”
mentioning
confidence: 99%